CaMKII may regulate renal tubular epithelial cell apoptosis through YAP/NFAT2 in acute kidney injury mice - Zongshun Huang; Yonghua Peng; Guibao Ke; Yun Xiao; Yaqi Chen (Renal Failure)
Aim Renal tubular epithelial cell (RTEC) apoptosis is important in acute kidney injury (AKI). Calcium/calmodulin-dependent protein kinase II (CaMKII) plays an important role in cell apoptosis, but its potential role in AKI remains unknown.Methods Using co-immunoprecipitation, immunofluorescence, immunohistochemistry, western blotting, flow cytometry, and cell transfection, this study aimed to verify whether CaMKII is involved in RTEC apoptosis and to explore the underlying mechanism.Results We found that CaMKII was involved in RTEC apoptosis. In adriamycin-induced AKI mice, serum creatinine levels, cell apoptosis, CaMKII activity, and nuclear factor of activated T cells 2 (NFAT2) levels increased, whereas nuclear Yes-associated protein (YAP) expression decreased; inhibition of CaMKII activity reversed these changes. Phosphorylated CaMKII could bind to phosphorylated YAP in the cytoplasm and block it from entering the nucleus, thereby failing to inhibit NFAT2-mediated cell apoptosis. Sequestrated phosphorylated YAP in the RTEC cytoplasm was finally degraded by ubiquitination.Conclusion CaMKII may regulate RTEC apoptosis through YAP/NFAT2 in AKI mice. CaMKII may be a potent molecular target for AKI treatment.